Pleasure over pressure: Hedonic motivation, peer influence, ‎and gender in Generation Z teachers’ compulsive buying - Sisriyenti; Efni Cerya (Yayasan Darussalam Bengkulu, 2026)
Compulsive buying is a growing concern among young Indonesian professionals as digital commerce expands. Peer influence, rumination, and hedonic motivation have been studied separately, but rarely together in one gender-moderated model for teachers. This cross-sectional survey examined their association with compulsive buying among Generation Z civil-servant teachers in Pesisir Selatan Regency, West Sumatra, drawing on conspicuous consumption theory and the I-PACE model. Of 731 eligible teachers holding PNS or PPPK status, 310 completed the questionnaire and were analysed with PLS-SEM in SmartPLS using a product-indicator interaction. Hedonic motivation showed the strongest association with compulsive buying (β = .775, 95% CI [.716, .834], p < .001), followed by peer influence (β = .218, 95% CI [.129, .307], p < .001). Rumination was not significantly associated (β = .034, 95% CI [-.053, .121]), nor was gender directly (β = .032, 95% CI [-.044, .108]) or as a moderator of any pathway. The model explained 75.5% of the variance in compulsive buying scores (adjusted R² = .749; Q² = .294). Because eligibility required at least three recent online purchases and the gender groups were unequal (243 women, 67 men), the estimates are conditional associations within a selected sample rather than causal effects, and the non-significant interactions are inconclusive rather than evidence of gender similarity. The findings suggest that pleasure-oriented and socially visible consumption warrants attention in teacher financial-wellbeing programmes.